The Profitability of Using Chinese Yuan in Carry Trade - Ali, Musaed S. Al; ElDukair, Zaina Z. (International Journal of Economics and Financial Modelling, 2017)
Carry trade is considered to be the most popular foreign exchange speculation strategy. Carry traders take advantage of interest rate differential to make profit. It has been well documented that this strategy is very rewarding. This paper examines the profitability of using the Chinese yuan as investment currency against the two most popular funding currencies, the Japanese yen and the Swiss franc in carry trade. The results obtained from this paper showed that the use of Chinese yuan produced positive returns.